PERILAKU INVESTOR PASAR MODAL DALAM MELAKUKAN TRANSAKSI SAHAM DI PASAR MODAL - Fahira Dhea Azzahra; Isni Andriana; Kemas M Husni Thamrin (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2021)
ABSTRACTThis study aims to analyzing the behavior of Palembang investors through cognitive biases and emotional biases that impacting investor’s decision making on stock transaction in the capital market. The population of the study are investors whom became partners of securities, those listed in Indonesian Stock Exchange and the securities which stand only in Palembang region. There are 50 investors as sample of this study with purposive sampling as sampling method. The type data of this study is qualitative and the resources of data in this study is primary data with distributing questionnaire. Analyzing method in this study using multivariate analysis Structural Equation Model (SEM) and the result of this study shows that availability bias, conservatism bias, and loss aversion bias have significance effect to Palembang investor’s decision making in 2020. For future research could be able to take other samples from another big cities, as well as conducted research on the relationship between behavioral biases and financing or behavioral biases and health that including demographics and etc.